Quantum Damped Mechanical Oscillator - Akpan N. Ikot; Louis E. Akpabio; Ita O. Akpan; Michael I. Umo; Eno E. Ituen (International Journal of Optics)
The exact solutions of the Schrödinger equation for quantum damped oscillator with modified Caldirola-Kanai Hamiltonian are evaluated. We also investigate the cases of under-, over-, and critical damping.